The effects of art therapy on Parkinson's and Alzheimer's disease Učinci art terapije na Parkinsonovu i Alzheimerovu bolest - Junaković, Alisa; Telarović, Srđana (2021)
Art therapy is one of the non-pharmacological treatment modalities for many diseases, including neurological and psychiatric disorders. Adrian Hill started art therapy in the 1940s. Parkinson`s disease is one of the progressive neurodegenerative diseases characterized by various motor and non-motor symptoms. As patients with Parkinson`s disease often report low quality of life despite improving their motor symptoms, complementary therapy may reduce their difficulties. Music and dance therapy, clay manipulation therapy, and tai chi training have promising results. There is also art therapy for one of the most common causes of dementia worldwide, Alzheimer`s disease. In addition to standard pharmacological treatment for Alzheimer`s disease e.g. cholinesterase inhibitors, music and visual arts therapy are evolving. This article presented some of the art therapy methods used in the most common neurodegenerative disorders, Parkinson`s and Alzheimer`s. In addition, we also presented some of the limitations of those studies. Some of the limitations are as follows: small sample size, relatively short duration of therapy sessions, and the fact that it is doubtful that art therapy could improve symptoms and cognitive abilities of people with advanced forms of neurodegenerative disorders.
Art terapija jedna je od nefarmakoloških metoda liječenja mnogih bolesti, pa tako i neuroloških i psihijatrijskih. Adrian Hill započeo je provođenje art terapije u četrdesetim godinama dvadesetog stoljeća. Parkinsonova bolest progresivna je neurodegenerativna bolest koju obilježavaju brojni i raznoliki motorički i nemotorički simptomi. Pacijenti koji boluju od Parkinsonove bolesti često imaju slabiju kvalitetu života unatoč poboljšanju motoričkih simptoma, a komplementarna terapija potencijalno može umanjiti njihove tegobe. Terapija glazbom i plesom, terapija glinom i tai chi trening daju obećavajuće rezultate. Također, postoji i art terapija za jednu od najpoznatijih i najčešćih vrsta demencija, Alzheimerovu bolest. Uz standardnu farmakološku terapiju za liječenje Alzheimerove bolesti poput inhibitora kolinesteraze, u posljednje vrijeme razvijaju se i različiti oblici art terapije poput terapije glazbom. U ovome radu predstavili smo neke od oblika art terapije koji se koriste u najčešćim neurodegenerativnim bolestima, Parkinsonovoj i Alzheimerovoj bolesti. Također smo prikazali i određena ograničenja studija o učinku same art terapije, kao što su mali uzorak ispitanika, relativno kratko trajanje terapijskih procesa te činjenica da nije izgledno da art terapija može pomoći ljudima koji već boluju od uznapredovalog oblika neurodegenerativne bolesti.
Bibliografija: 37 jed.
Abstract ; Sažetak.
Keywords: Alzheimerova bolest -- Demencija -- Parkinsonova bolest -- Art terapija -- Kvaliteta života -- Bazalni gangliji